IJCM_345A: Attitudes and Beliefs among Young Adults in Urban Meerut towards Depression: A Cross-Sectional Study - Bargayary Harimu; Jain Seema; Kumar Sanjeev (Wolters Kluwer Medknow Publications, 2024)
Background: About 70 % of mental disorders can be diagnosed prior to age 25 years and they comprise the single largest component of disease burden during the second decade of the life span. Globally, Depression is one of the leading causes of disability. WHO estimates that the burden of mental health problems in India is 2443 disability-adjusted life years (DALYs) per 100 00 population. The economic loss due to mental health conditions, between 2012-2030, is estimated at USD 1.03 trillion. There has been an increased rise in the need for improved mental health literacy to address the complex issues surrounding mental well-being. Objective: To explore the attitudes and beliefs and its influencing factors among the young adults of urban Meerut towards Depression. Methodology: It is a community based cross-sectional study done among the 18-25 years age group residents of urban Meerut. The sample size was calculated to be 188 which was rounded off to 190, at 95% confidence interval with 6.5% absolute precision following a prevalence of 29.04% from a similar type of study. Data was collected using semi-structured questionnaire designed based on National Survey of Mental Health Literacy and Stigma Youth Boost Survey V5 by Anthony F. Jorm and Nicola Reavley. Results: In the current study, it was found that about 32.6% (62) of the study participants did not consider depression as a real medical illness. However, it was seen that majority i.e. 90.0% (171) had believed that if that sharing with the close family/friends could help in recovering from depression. Conclusion: By promoting accurate education, responsible media portrayals, personal storytelling, and community engagement towards developing positive public attitudes towards mental health conditions will hold significant power in influencing societal perceptions, shaping interactions, and impacting the well-being of individuals.